Diabetic Retinopathy and Ayurvedic Palliative Therapies: A Comprehensive Review (Academia Journal of Medicine, 2025)
Diabetic retinopathy (DR) is one of the most common microvascular complications  of diabetes mellitus and a leading cause of preventable blindness globally. Despite  advancements in modern ophthalmology, current treatment options are often  invasive and expensive, leading to an increased interest in complementary and  alternative therapies, especially Ayurveda.
Keywords: Diabetes Mellitus; Neuropathy